White Collar Subcontracted Employees in the Public Health Sector: The Case of Fırat University Hospital - Sinan Acar (Journal of Economy Culture and Society)
With the Health Transformation Program (HTP) in Turkey whose infrastructure was established in the 1980s and came into practice in 2003, a significant stage of the neo-liberal transformation process started in the field of public health services. With the transformation process in health, a transition was made into performance- based service production in healthcare services, and flexible forms of employment started to be seen in employment processes. This study mainly focuses on the perception and experience of the white- collar subcontracted employees in public health services of flexible and precarious employment in the neoliberal period. As a result, it was observed that most participants were young, single and graduates of higher education. It was found that the knowledge, skills and experience of the employees were not considered in decision-making processes, and accordingly, they had lower levels of feelings of organizational justice. It may be stated that, due to the production of services with flexible and performance based work, the workload of the employees has increased considerably and the work is carried out with a low number of employees. Having employees with the same job and similar educational levels under different forms of employment was found to reveal material and moral inequalities among the employees. Consequently, the neo-liberal transformation process in public health services also shows its effect on the employment processes in these fields and the existing structure is being transformed in a way to also involve white-collar occupations by taking contracts, flexibility and precarity as a basis.